CdS Nanoparticles with a Thermoresponsive Polymer: Synthesis and Properties. (14th June 2012) - Khan, Aslam
Abstract : This paper describes the synthesis of thermoresponsive colloidal nanocomposites based on CdS and poly( N -isopropylacrylamide). The CdS nanoparticles were prepared at room temperature from cadmium chloride and sodium sulfide salts in the presence of an organic ligand, 3-mercaptopropionic acid (MPA). The as-prepared MPA-bound CdS nanoparticles were stable for more than 30 days and exhibited good optical properties. The effect of various ratios of MPA/Cd 2+ and H2 O/DMF (dimethylformamide) on the particle size of the CdS nanoparticles was investigated using UV-vis absorption measurements. Transmission electron microscopy studies showed that the particle sizes were approximately 4 nm in diameter, which is consistent with the size obtained using UV-vis spectroscopy. The CdS nanocomposite showed a temperature-responsive phenomenon as its temperature increased from 20 to 45°C.